Islamic Business Ethics In Development MSMEs in Society - Nuhaeni; Isma Nawaitul Ihram; Abdul Fajar; Hardiyanti Ridwan (www.amertainstitute.com, 2024)
This article discusses the role of Islamic business ethics in driving the growth of Micro, Small, and Medium Enterprises (MSMEs), focusing on principles such as honesty, justice, social responsibility, and sustainability. Using a qualitative approach, the research explores how MSME actors can apply Islamic values to build customer trust, strengthen business relationships, and contribute to social welfare. The findings show that integrating Islamic business ethics not only enhances the competitiveness of MSMEs but also positively impacts local economic development. By adhering to ethical values like fairness and social responsibility, MSMEs can foster a strong sense of community, loyalty, and long-term sustainability. These values help businesses maintain ethical practices while achieving profitability, which in turn supports the welfare of society. The study underscores that the implementation of Islamic business ethics is a strategic element in creating a business ecosystem focused on blessings and sustainability. It demonstrates that businesses guided by these values are more likely to thrive in the long term while making meaningful contributions to their communities and local economies. Future research could examine specific case studies of MSMEs that have successfully integrated Islamic ethics to assess the broader impact on regional economic growth and social welfare.